2018
DOI: 10.1002/eco.1963
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effect of beaver and human‐made impoundments on stream zooplankton

Abstract: Small human‐made dams and beaver ponds cause significant changes in the environment of small streams. The decreased current velocity and increased water retention time in these impoundments favour the development of limnetic organisms, for example, zooplankton. However, small human‐made reservoirs are regulated, deep and narrow, whereas beavers create relatively large impoundments with numerous shallow patches and their impact on the stream zooplankton communities can be different. We compared the effect of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Hence, even a small dam that created a very shallow reservoir caused a significant difference in the richness and abundance of zooplankton between the upstream and the downstream sections. A similar pattern of the distribution of the zooplankton community was reported in small forest streams and rivers impounded by human-made dams or beaver dams in some studies [7,10,14,21]. We observed that in the impoundment (POND)-the "Słoneczne lake" of Bukówka-the richness and abundance of zooplankton were high, which was comparable to or even exceeded those in the typical temperate limnetic basins (e.g., eutrophic lakes or reservoirs) [22,23].…”
Section: Zooplanktonsupporting
confidence: 86%
See 1 more Smart Citation
“…Hence, even a small dam that created a very shallow reservoir caused a significant difference in the richness and abundance of zooplankton between the upstream and the downstream sections. A similar pattern of the distribution of the zooplankton community was reported in small forest streams and rivers impounded by human-made dams or beaver dams in some studies [7,10,14,21]. We observed that in the impoundment (POND)-the "Słoneczne lake" of Bukówka-the richness and abundance of zooplankton were high, which was comparable to or even exceeded those in the typical temperate limnetic basins (e.g., eutrophic lakes or reservoirs) [22,23].…”
Section: Zooplanktonsupporting
confidence: 86%
“…It is generally known that zooplankton disperse passively from the outlet of stagnant basins to downstream and can colonize new habitats [27]. Drifting zooplankton can colonize the river if its bed offer zones with low current velocity or with stagnant water (e.g., slack waters, impoundments, and floodplains) [7,10]. The main variables that contribute to the increase in the richness and abundance of zooplankton in the Bukówka stream at the more downstream sites are as follows: a decrease in the current velocity, a longer water retention time or greater areas of open-water zones, higher number of slack water areas, covering of floodplains by macrophytes, and adjacent water bodies [14,28,29].…”
Section: Zooplanktonmentioning
confidence: 99%
“…Also zooplankton transfer from lakes and reservoirs into the river is well documented (e.g., Basu & Pick, 1997 ; Pourriot, Rougier & Miquelis, 1997 ; Czerniawski & Domagala, 2014 ). Drifting zooplankton can colonize the river if its bed offer zones with low current velocity or with stagnant water e.g., slackwaters, impoundments, floodplains ( Czerniawski & Sługocki, 2017 ; Czerniawski & Sługocki, 2018 ). The Barycz is a kind of impoundment–cascade system in which richness and abundance of zooplankton increase with the number of dams.…”
Section: Discussionmentioning
confidence: 99%
“…However, hydrological changes, such as lower current velocity or an increase of nutrient content, and higher temperatures in small rivers provide atypical yet favorable conditions for zooplankton growth. Zooplankton reacts rapidly to the hydrological changes in rivers, increasing its richness and abundance [13,14]. This certainly depends on the reservoir characteristics, and specifically its hydrological conditions, which consequently can change biological conditions and favor the development of planktonic organisms that cannot resist stronger water currents.…”
Section: Introductionmentioning
confidence: 99%
“…The more severe the changes upstream, the stronger the effects downstream [2]. Zooplankton was one of the indicators for these changes [6,14]. However, the functioning of a small lowland river depends on different values of hydrological factors than that of mountain rivers.…”
Section: Introductionmentioning
confidence: 99%